Green Synthesis of S- and N-Codoped Carbon Nanospheres and Application as Adsorbent of Pb (II) from Aqueous Solution - Nadia Hussain; Salam Alwan; Hassan Alshamsi; Ibrahim Sahib (International Journal of Chemical Engineering)
In this paper, green and facile synthesis of sulfur- and nitrogen-codoped carbon nanospheres (CNs) was prepared from the extract of Hibiscus sabdariffa L by a direct hydrothermal method. Finally, sulfur-carbon nanospheres (CNs) were used as the adsorbent to remove Pb+2 ions from aqueous solutions because of the high surface area of S-CNs from CNs and N-CNs. The synthesized nanospheres were examined by Fourier transform infrared (FTIR) spectroscopy, X-ray diffraction (XRD), field emission scanning electron microscopy, transmission electron microscopy (TEM), and nitrogen adsorption-desorption isotherms. The results show spherical shapes have a particle size of up to 65 nm with a high surface area capable of absorbing lead ions efficiently. Additionally, the factors affecting the process of adsorption that include equilibrium time, temperature, pH solution, ionic intensity, and adsorbent dose were studied. The equilibrium removal efficiency was studied employing Langmuir, Freundlich, and Temkin isotherm forms. The kinetic data were analyzed with two different kinetic models, and both apply to the adsorption process depending on the values of correlation coefficients. The thermodynamic parameters including Gibbs free energy (ΔG°), standard enthalpy change (ΔH°), and standard entropy change (ΔS°) were calculated for the adsorption process.